Packaging design as communicator of product attributes : effects on consumers' attribute inferences - van Ooijen, Iris, ....- (Amsterdam : SWOCC, 2016)
Despite its growing importance in the market place, packaging design as a persuasive cue is understudied in the consumer behavior literature. Althought the effect of explicit packaging cues on food attribute perception has been studied extensively, systematic research on the effect of packaging desgin cues on food attribute perception is still in its infancy. This dissertation demonstrates that packaging design elements such as shape and colour affect consumers' inferences regarding food product attributes in several ways. Hence, it is demonstrated that packaging desing is not merely a 'vehicle' for explicit cues such as claims and logos, but also has communicative power in itself.